Information acquisition, signaling and learning in duopoly - Thomas D. Jeitschko; Ting Liu; Tao Wang (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2016)
We study firms' incentives to acquire private information in a setting where subsequent competition leads to firms' later signaling their private information to rivals. Due to signaling, equilibrium prices are distorted, and so while firms benefit from obtaining more precise private information, the value of information is reduced by the price distortion. Thus, compared with firms that do not attempt to manipulate rivals' beliefs, signaling firms acquire less precise information. An industry-wide trade-association acquiring information increases firm profit and may also increase consumer surplus, so allowing such collective action may be in the interest of regulatory authorities.
Keywords: D4; D8; L1; 330; information acquisition; signaling; product differentiation